CHRONIC KIDNEY DISEASE AND CEREBROCARDIOVASCULAR COMPLICATIONS IN ARTERIAL HYPERTENSION: RESULTS OF PERINDOPRIL А USAGE WITH INDAPAMID - V. G. Shemetova; G. M. Orlova; A. L. Nebesnykh; E. S. Markhanova (Российский кардиологический журнал)
Aim. To evaluate the development of cardio- and cerebrovascular complications in arterial hypertension depending on presence or absence of kidney injury, to evaluate organoprotective activity of perindopril with indapamide (the medications Noliprel A and Noliprel A Forte).Material and methods. The three-year prospective investigation has been performed on 52 outpatients with AH. The diagnosis of CKD was set according to KDOQI 2002 guidelines. All patients received antihypertensive therapy with Noliprel 2,5 + 0,625 mg (Noliprel A) — (10) or 5 + 1,25 mg (Noliprel A Forte) — (42). Control group — 25 patients on antihypertensive treatmient without Noliprel. Primary endpoint was the development of CKD or worsening of already persisting CKD to the next stage. Secondary endpoints: cardio- and cerebrovascular accident (myocardial infarction, ischemic stroke, transitory ischemic attack). Results. In the group of therapy with combination of perindopril A with indapamide primary endpoint was reached by 12 (23%) patients, in the group without this combination in 12 (48%) patients, p=0,05. Regression of severity of CKD was marked in 5 (15,5%) patients in the main group and in no one in comparison group.In the main group with CKD the cardiocerebral events occured in 11 (33,3%) patients, in the group without kidney injury in 1 (5,25%) patient had cardiocerebral event, p<0,05. Between the main and the comparison groups there are also significant differences by the prevalence of myocardial infarction and ischemic stroke: 12 (23%) vs. 14 (56%), p=0,009. In the group of patients not taken combination of perindopril A with indapamide, cardiovascular accidents occur almost 10 times more often than in the main group without CKD, and almost 2 times more often than in CKD group with drug combination.Conclusion. Prospective observation has shown higher prevalence of ischemic stroke and transient ischemic attack, and cardiovascular accidents in the group of patients with chronic kidney disease comparing to the group without kidney injury. Dynamic observation of the AH patients, use of perindopril+indapamide combination allows to reach antihypertensive and organoprotective aim.